2020
DOI: 10.1007/s11665-020-04904-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Corrosion Behavior of Direct Metal Laser Sintered Ti-6Al-4V for Biomedical Applications

Abstract: In this study, the effects of microstructure, surface roughness, and surface porosity on the corrosion behavior of direct metal laser sintered (DMLS) Ti-6Al-4V were experimentally investigated. The electrochemical measurements were conducted using a three-electrode setup setting, with the specimens in RingerÕs solution at 37°C. The acicular microstructure in the DMLS Ti-6Al-4V samples resulted in greater corrosion resistance than that of the Grade 5 alloy with an equiaxed microstructure. Electrochemical study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…TA1 material has strong antioxidant properties and stable tissue, and the printed workpiece has good mechanical properties and is used in the biomedical industry to create implants with the same excellent mechanical properties as bone. Compared with other alloys, TA1's elastic modulus is closest to human bone, and it has good biocompatibility without causing adverse reactions in the human body [19][20][21][22].…”
Section: Experimental Raw Materialsmentioning
confidence: 99%
“…TA1 material has strong antioxidant properties and stable tissue, and the printed workpiece has good mechanical properties and is used in the biomedical industry to create implants with the same excellent mechanical properties as bone. Compared with other alloys, TA1's elastic modulus is closest to human bone, and it has good biocompatibility without causing adverse reactions in the human body [19][20][21][22].…”
Section: Experimental Raw Materialsmentioning
confidence: 99%
“…The Italian "Tixos" implant, which is similar to a traditional implant, is produced by DMLS technology and has a variety of sizes to choose from (Mangano et al, 2012a). Furthermore, implants produced by DMLS have high fatigue strength and good corrosion resistance (Yang et al, 2020). Gehrke et al confirmed that the mean fracture strength of DMLS implants with diameter 3.5 mm and length 16 mm can reach >1200 N (Gehrke et al, 2018): However, for two-stage dental implants, it is difficult to achieve a tight connection between a 3D printed implant and the abutment due to a lack of surface accuracy, but a tight connection can be achieved by machining of the connection structure in the 3D printing implant platform (Tunchel et al, 2016).…”
Section: Dental Implantsmentioning
confidence: 99%
“…Ti-6Al-4V alloy is a well-known material for many biomedical applications due to its excellent mechanical properties, good corrosion resistance, biocompatibility, and light-specific weight [ 1 , 2 , 3 ]. Ti-6Al-4V is a double-phase (α + β) titanium alloy.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that alloy corrosion resistance could be improved by adding the Cu element [ 24 ]. Some researchers reported the corrosion resistance of SLM Ti-6Al-4V was noticed to be higher due to the presence of relatively higher β content in comparison to the wrought Ti-6Al-4V [ 25 ], although the failure of titanium alloys in medical implants is known to be induced by pitting and crevice corrosion [ 3 ]. Further surface modification of dental implants plays a significant role in obtaining more bio-functional materials.…”
Section: Introductionmentioning
confidence: 99%